In vitro reactivation potency of acetylcholinesterase reactivators--K074 and K075--to reactivate tabun-inhibited human brain cholinesterases - Kuca, Kamil; Cabal, Jiri; Jun, Daniel; Musilek, Kamil (Neurotoxicity research, 2007)
In this work, two oximes for the treatment of tabun-inhibited acetylcholinesterase (AChE; EC 3.1.1.7), K074 (1,4-bis(4-hydroxyiminomethylpyridinium)butane dibromide) and K075 ((E)-1,4-bis(4-hydroxyiminomethylpyridinium)but-2-en dibromide), were tested in vitro as reactivators of AChE. Comparison was made with currently used AChE reactivators (pralidoxime, HI-6, methoxime and obidoxime). Human brain homogenate was taken as an appropriate source of the cholinesterases. As resulted, oxime K074 appears to be the most potent reactivator of tabun-inhibited AChE, with reactivation potency comparable to that of obidoxime. A second AChE reactivator, K075, does not attain as great a reactivation potency as K074, although its maximal reactivation (17%) was achieved at relevant concentrations for humans.
Keywords: aktivace enzymů; Acetylcholinesterase; butany; Enzyme Activation; oximy; In Vitro Techniques; Pyridinium Compounds; nucleus caudatus; techniky in vitro; lidé; pyridinové sloučeniny; Pralidoxime Compounds; Butanes; Caudate Nucleus; pralidoximové sloučeniny; Oximes; Obidoxime Chloride; acetylcholinesterasa; organofosfáty; reaktivátory cholinesterasy; obidoxim chlorid; cholinesterasové inhibitory; Cholinesterase Inhibitors; Organophosphates; Cholinesterase Reactivators; Humans